Modifications to the TRNSYS Thermal Storage Tank Model - Schmid, Michael (University of Wisconsin-Madison, 1994)
Solar energy is a time-dependent energy resource. The demands for energy are also time dependent but in a different fashion than the solar energy supply. Consequently, energy has to be stored if solar energy is to meet substantial portions of these energy needs. One of the most economically feasible methods of solar storage is a fluid storage tank. Before choosing the proper size and performance of a thermal fluid storage, it is important to make calculations with the whole system. The TRNSYS software package has been used extensively for thermal system analysis. It has a modular structure and consists of individual subroutines which represent real physical devices or utility components. The components can be connected together to form complex systems. One of these components is the TYPE 4 multi-node model. The tank is modeled as N fully mixed volume segments. The degree of temperature stratification, which increases the effectiveness of a storage tank, is determined by the choice of N. Higher values of N result in more stratification. Although the current TYPE 4 tank model has been proven to be an accurate component, it has some limitations. Outlet flows are fixed at the tank top (load flow) or tank bottom (collector flow). The tank has always two inlets and two outlets. Inlet flow rate from one source are automatically the outlet flow rate to the same source. The output of the losses to the exhaust of a gas auxiliary heater are added to the losses to the environment. Only tanks of circular cross section can be used. The goal of this project is to modify the current TYPE 4 model. The new TYPE 4 includes several new features which make the tank more versatile. Inlet and outlet positions can be located anywhere in the tank. Inlet flow rates from one source do not have to be automatically equal the outlet flow rate. Also the tank need not have two inlets and two outlets; it can have less than four flows, and still satisfy a mass balance for the whole tank. The losses to the exhaust flue of an optional gas auxiliary heater are output separately from the losses to the environment. The cross section of the tank can be circular or rectangular. The new model calculates the difference in static pressure between the top of the tank and each inlet and outlet position. This option is needed to simulate a thermosiphon system. Further, the conduction between the tank segments (nodes) is considered. Since tanks may destratify more rapidly due to natural convection a user specified parameter has been added to the conduction coefficient.
73pp.
Keywords: Thesis (Diplomarbeit)--University of Wisconsin--Madison, 1994.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.